PELATIHAN PEMANFAATAN DIGITAL PARENTING CONTROL MENGGUNAKAN GOOGLE FAMILY LINK PADA IBU TAMAN KAMPUNG TANGGUH (Jurnal AbdiMas Nusa Mandiri, 2024)
The use of digital technology is increasingly widespread in the modern era, which is changing the way parents educate their children. "Google Parenting" emerged as a term that reflects parents' efforts to face the challenges of parenting in the digital era. This concept emphasizes the importance of parents understanding the impact of technology on children's development as well as appropriate development strategies to use it wisely while maintaining balance in family life. This service activity aims to provide understanding to parents about using the Google Family Link application. The first stage includes theoretical explanations, direct practice using the application, and interactive discussions. The material is delivered through multimedia techniques using a laptop and the internet. This activity is not only informative but also involves active participants through modules, pretests, posttests and discussions. The results of the training for PKK RW 012 Taman Kampung Tangguh mothers showed an increase in their awareness and understanding of digital risks for children as well as their ability to control children's online activities. This helps reduce the risk of exposure to age-inappropriate content and improves communication between mother and child regarding digital safety.
Keywords: gadgets; google family link; parenting control